2022
DOI: 10.1590/1519-6984.227703
|View full text |Cite
|
Sign up to set email alerts
|

Role of beneficial microbes with nitrogen and phosphorous levels on canola productivity

Abstract: A research was conducted to evaluate the impact of various nitrogen and phosphorus levels along with beneficial microbes to enhance canola productivity. The research was carried out at Agronomy Research Farm, The University of Agriculture Peshawar in winter 2016-2017. The experiment was conducted in randomized complete block factorial design. The study was comprised of three factors including nitrogen (60, 120 and 180 kg ha-1), phosphorous (70, 100 and 130 kg ha-1) and beneficial microbes (with and without BM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…An elevated nitrogen concentration is associated with an increased CO2 assimilation rate and stomatal conductance in the crop, which aids in producing chlorophyll and green pigments. For example, Muhammad, Alam [61] conducted a related study to evaluate the impact of various nitrogen and phosphorous levels and beneficial microbes on enhancing canola productivity. The results revealed that nitrogen applied at a rate of 180 kg ha −1 increased plant pods, seed pods, the seed-filling duration, seed weight, biological yield, and seed yield.…”
Section: Nus Crop Attributes That Have Been Remotely Sensed Using Dro...mentioning
confidence: 99%
“…An elevated nitrogen concentration is associated with an increased CO2 assimilation rate and stomatal conductance in the crop, which aids in producing chlorophyll and green pigments. For example, Muhammad, Alam [61] conducted a related study to evaluate the impact of various nitrogen and phosphorous levels and beneficial microbes on enhancing canola productivity. The results revealed that nitrogen applied at a rate of 180 kg ha −1 increased plant pods, seed pods, the seed-filling duration, seed weight, biological yield, and seed yield.…”
Section: Nus Crop Attributes That Have Been Remotely Sensed Using Dro...mentioning
confidence: 99%